Protection of Fundamental Rights by Constitutional Courts - A Comparative Perspective - Patrono, Mario (Victoria University of Wellington Law Review, 2000)
"Man", said Benjamin Franklin, "is a tool-making animal". A major contribution of 20th century Western legal thought to tool-making was possibly the publication in 1914 of Reichgesetz und Landesgesetz nach der österreichen Verfassung1 by Hans Kelsen, a Czech lawyer, but Austrian by adoption. Kelsen is noted for his "pure theory of law". By conferring upon a special constitutional court the exclusive power to rule on the constitutionality of legislation and to refuse to enforce legislation that in its judgment violated the constitution, Kelsen found a way for the United States pattern of constitutional adjudication (as established in 1803 by Chief Justice John Marshall in Marbury v Madison) to work in countries which have (as in the United States) a written and "rigid" Basic Law, and even where the doctrine of precedent does not operate. This is a very short history of the development of that Kelsen "tool" and an evaluation of it.